The Relationship between Golgi Protein 73, Alpha-Fetoprotein, Liver Function Indicators, and Traditional Chinese Medicine Syndrome Types of Primary Liver Cancer - Lu, Baoping; Rong, Jinxia; Liu, Huaimin (Chinese medicine and natural products, 2023)
Objective Our objective was to analyze the correlation between Golgi protein 73 (GP73), alpha-fetoprotein (AFP), liver function indicators, and traditional Chinese medicine (TCM) syndrome types of primary liver cancer (hereinafter referred to as “liver cancer”).Methods In total, 156 liver cancer patients (liver cancer group) and 52 healthy individuals (health group) were selected as the research subjects to detect their GP73, AFP expression, and liver function-related indicators. The obtained data were statistically analyzed using SPSS 21.0 software.Results (1) The positive expression rate of GP73 in the liver cancer group was 50%; the positive expression rates of qi stagnation and blood stasis syndrome, heat toxin in liver and gallbladder syndrome, and yin deficiency of liver and kidney syndrome were 37.9, 54.3, and 59.6%, respectively. There was no statistically significant difference between the groups (p > 0.05). The positive expression rate of AFP was 50%. The positive expression rates of qi stagnation and blood stasis syndrome, heat-toxin in liver and gallbladder syndrome, and yin deficiency of liver and kidney syndrome were 41.7, 54.3, and 59.6%, respectively. There was a statistically significant difference between the groups (p < 0.05). (2) The GP73 levels of patients with different syndrome types in the liver cancer group were ranked from high to low as yin deficiency of liver and kidney syndrome, heat toxin in liver and gallbladder syndrome, and qi stagnation and blood stasis syndrome. The differences between the groups were statistically significant (p < 0.05). The AFP levels of patients with different syndrome types in the liver cancer group were ranked from high to low as heat toxin in liver and gallbladder syndrome, yin deficiency of liver and kidney syndrome, and qi stagnation and blood stasis syndrome. There was no statistically significant difference between the groups (p > 0.05). (3) Analysis of liver function indicators in the liver cancer group: the alanine transaminase (ALT) levels of patients with different syndrome types were in descending order from high to low, including yin deficiency of liver and kidney syndrome, heat toxin in liver and gallbladder syndrome, and qi stagnation and blood stasis syndrome. The differences between groups were statistically significant (p < 0.05). The aspartate aminotransferase (AST) levels of patients with different syndrome types were ranked from high to low as follows: heat toxin in liver and gallbladder syndrome, yin deficiency of liver and kidney syndrome, and qi stagnation and blood stasis syndrome. The difference between groups was statistically significant (p < 0.05). The levels of albumin (ALB) in patients with different syndrome types were ranked from high to low, including heat toxin in liver and gallbladder syndrome, qi stagnation and blood stasis syndrome, and yin deficiency of liver and kidney syndrome. The differences between groups were statistically significant (p < 0.05).Conclusion GP73 and indicators such as ALT, AST, and ALB are of great significance in the diagnosis of TCM syndrome differentiation and classification of liver cancer patients.
Keywords: primary liver cancer; Golgi protein 73; alpha-fetoprotein; liver function; TCM syndrome types